New acaricide toxicity on tetranychus urticae koch, selectivity and side effect evaluations on the predatory mite phytoseiulus persimilis athias-henriot (Acari: Phytoseiidae) - Diab, Hanan Salah El-Din Taha (Current Research in Agricultural Sciences, 2023)
The novel mode of action and newer pesticides product molecules is a promising component for agriculture management programs. For this argument some acaricide toxicity evaluations were completed on the predatory mite Phytoseiulus persimilis Athias-Henriot (Acari: Phytoseiidae) in laboratory rearing for two generation under acaricide sublethal effect. Toxicity results showed that chlorfenapyr was the most toxic acaricide for Tetranychus urtica Koch and etoxazole was the lesast and for P. persimilis, etoxazole was the most toxic and fenproxymat was the least. Relative toxicity recorded was higher in etoxazole and fenproxymat (7.916 and 5.058 times) respectively. Selectivity data approved that abamectin was the most selective acaricide and etoxazole was the least (8.24 and 0.268) respectively. Effect on first generation of P. persimilis growth fertility and productivity declined, consequently, R0 and rm values where in LC25 attained values ranged from 0.59 to 0.66 for cyflumetofene and hexythiazox, ri data ranged from 0.29 to 0.36 for fenproxymate and cyflumetofene and R0 ranged from 0.53 to 6.0 for cyflumetofene and hexythiazox respectively. But in the second generation similar results attained because declined toxicity where rm in LC25 was from 0.93 and 1.13 for fenproxymat and etoxazole and in LC50 was 0.90 and 1.18 for cyflumetofene and hexythiazox respectively. A high effect on No of eggs /female/day produced, shortened in total time of the generation at LC50 level of treatment more than LC25, and sex ratio resulted more male number emerged than female. The high acaricide concentrations used can kill more T.urtica than P.persimilis.